Culture, Heritage and Territorial Identities for Urban Development - Cercleux, Andreea-Loreta; Harfst, Jörn; Ilovan, Oana-Ramona (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
From the 1970s onwards, many towns and cities have experienced deindustrialization processes, while seeing a gradual growth of tertiarization and diversification of services, including cultural ones. With the different, both positive and negative, effects introduced by new cultural interpretations of cities (e.g., culture in public spaces, cultural and creative industries, culture as marketing tools, cultural commodification, etc.), the concept of culture has become increasingly associated with urban image and identity. In finding solutions within regeneration processes, policies often rely on tools from the cultural and creative fields. Additionally, built material and immaterial heritage can have significant roles: e.g., by converting heritage sites and buildings through cultural projects or new functions, or capitalizing on specific traditions and place memory for local identity and place attachment. This SI focuses on cultural approaches in connection with urban development and gather contributions from various research fields. It addresses researchers and academics from social sciences who are interested in topics such as: cultural activities and their role in urban development; cities (re)constructing their identity; culture as a relevant component of current spatial planning policies; urban strategies, attracting creative people; urban image, heritage and culture; culture, local memory and local identities; heritage and industrial culture; subcultures within cities and processes of urban change.